KERJASAMA INDONESIA DAN INTERNATIONAL LABOUR ORGANIZATION DALAM MELINDUNGI WNI SEBAGAI PEKERJA MIGRAN DI MALAYSIA MELALUI PROGRAM DECENT WORK COUNTRY PROGRAMMES (DCWP) - Oktaviandono Oktaviandono; Muhammad Zuhdi Syahputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
The state is obliged to guarantee rights, opportunities, and provide protection for every citizenwithout discrimination to get decent work and income, both at home and abroad in accordancewith their expertise, skills, talents, interests and abilities. So far, the government seems to be lessserious about protecting migrant workers, resulting in cases of human trafficking, slavery, forcedlabor, victims of violence, abuse, crimes against human dignity, and other treatments that violatehuman rights. For this reason, international cooperation is carried out to ensure the safety ofIndonesian Migrant Workers (IRC). One of the collaborations carried out is the collaborationbetween Indonesia and the International Labor Organization (ILO).Decent Work Country Program(DCWP) which serves to protect PMI in Malaysia, as one of the countries that receives the mostmigrant workers from Indonesia.